Immunogenicity of chimeric haemagglutinin-based, universal influenza virus vaccine candidates: interim results of a randomised, placebo-controlled, phase 1 clinical trial. Issue 1 (January 2020) - Bernstein, David I; Guptill, Jeffrey; Naficy, Abdollah; Nachbagauer, Raffael; Berlanda-Scorza, Francesco; Feser, Jodi; Wilson, Patrick C; Solórzano, Alicia; Van der Wielen, Marie; Walter, Emmanuel B; Albrecht, Randy A; Buschle, Kristen N; et al.
Summary: Background: Influenza viruses cause substantial annual morbidity and mortality globally. Current vaccines protect against influenza only when well matched to the circulating strains. However, antigenic drift can cause considerable mismatches between vaccine and circulating strains, substantially reducing vaccine effectiveness. Moreover, current seasonal vaccines are ineffective against pandemic influenza, and production of a vaccine matched to a newly emerging virus strain takes months. Therefore, there is an unmet medical need for a broadly protective influenza virus vaccine. We aimed to test the ability of chimeric H1 haemagglutinin-based universal influenza virus vaccine candidates to induce broadly cross-reactive antibodies targeting the stalk domain of group 1 haemagglutinin-expressing influenza viruses. Methods: We did a randomised, observer-blinded, phase 1 study in healthy adults in two centres in the USA. Participants were randomly assigned to one of three prime–boost, chimeric haemagglutinin-based vaccine regimens or one of two placebo groups. The vaccine regimens included a chimeric H8/1, intranasal, live-attenuated vaccine on day 1 followed by a non-adjuvanted, chimeric H5/1, intramuscular, inactivated vaccine on day 85; the same regimen but with the inactivated vaccine being adjuvanted with AS03; and an AS03-adjuvanted, chimeric H8/1, intramuscular, inactivated vaccine followed by an AS03-adjuvanted, chimeric H5/1, intramuscular, inactivated vaccine. In this planned interim analysis, the primary endpoints of reactogenicity and safety were assessed by blinded study group. We also assessed anti-H1 haemagglutinin stalk, anti-H2, anti-H9, and anti-H18 IgG antibody titres and plasmablast and memory B-cell responses in peripheral blood. This trial is registered with ClinicalTrials.gov, number NCT03300050 . Findings: Between Oct 10, 2017, and Nov 27, 2017, 65 participants were enrolled and randomly assigned. The adjuvanted inactivated vaccine, but not the live-attenuated vaccine, induced a substantial serum IgG antibody response after the prime immunisation, with a seven times increase in anti-H1 stalk antibody titres on day 29. After boost immunisation, all vaccine regimens induced detectable anti-H1 stalk antibody (2·2–5·6 times induction over baseline), cross-reactive serum IgG antibody, and peripheral blood plasmablast responses. An unsolicited adverse event was reported for 29 (48%) of 61 participants. Solicited local adverse events were reported in 12 (48%) of 25 participants following prime vaccination with intramuscular study product or placebo, in 12 (33%) of 36 after prime immunisation with intranasal study product or placebo, and in 18 (32%) of 56 following booster doses of study product or placebo. Solicited systemic adverse events were reported in 14 (56%) of 25 after prime immunisation with intramuscular study product or placebo, in 22 (61%) of 36 after immunisation with intranasal study product or placebo, and in 21 (38%) of 56 after booster doses of study product or placebo. Disaggregated safety data were not available at the time of this interim analysis. Interpretation: The tested chimeric haemagglutinin-based, universal influenza virus vaccine regimens elicited cross-reactive serum IgG antibodies that targeted the conserved haemagglutinin stalk domain. This is the first proof-of-principle study to show that high anti-stalk titres can be induced by a rationally designed vaccine in humans and opens up avenues for further development of universal influenza virus vaccines. On the basis of the blinded study group, the vaccine regimens were tolerable and no safety concerns were observed. Funding: Bill & Melinda Gates Foundation.